The quintessence of legal consciousness as a factor of deviant behavior - S. H. Pevko (Law and Safety)
A comprehensive analysis of the factors influencing legal awareness, which are the basis for deviant behavior has been conducted. The quintessence of the concepts of legal awareness and deviant behavior as two components of the causal relationship between the existence of facts of offenses in the state has been analyzed. The essence of legal consciousness, which is a complex component that has relevant parts, has been determined. Parts of legal consciousness together can reflect the rule of law in the state, but due to the inadequate level or lack of at least one of them there are facts of illegal behavior, i.e. behavior that has signs that do not meet the requirements of society. Behavior that contradicts the legal principles of public relations is deviant. Therefore, to analyze the factors influencing legal awareness, the essence of deviant behavior and its objective factors of existence in social relations have been determined. With the help of the analysis of judicial practice and legislation of Ukraine, a comprehensive review of both legal regulation and examples of the implementation of legal norms in life, reflecting the reality of the existence of the problem raised in the article has been made. In search of a solution to the issue of establishing the factors influencing legal awareness that cause deviant behavior, and ways to solve them, the theoretical aspects of this issue and real cases of their occurrence have been studied. As a result, it has been found that the factors influencing legal awareness that cause deviant behavior are inadequate level of legal education, which is manifested in the low level of legal psychology as a component of legal awareness; improper level of implementation of laws, which is expressed in legal nihilism as a reflection of the attitude to the requirements of the legal norms of citizens, legal entities and persons residing in Ukraine; and low economic level of the population. In this regard, appropriate ways to overcome this problem were proposed, namely the implementation of the programme of legal education of the population, continuous and professional implementation of legal requirements by the authorities and the development and implementation of public policy programmes to improve economic life.